Changes in habits: an analysis of body composition and nutrition in college - Pereira, Maykeel Avila V (2015)
Obesity in adolescence is predictive of adult obesity. Thus, we assessed the factors associated with obesity. This study aimed to identify the change in body composition between college students from 20. Were used as classification, body mass index, waist / hip ratio and fat percentage. Among the entire sample of students, 100% were active. Prevalence of overweight and normal BMI classification were 65% and 15% respectively in the evaluation, unlike the result of the revaluation, which was 35% of individuals classified as overweight. All men (07) are desirable compared to the percentage of fat.